Aggression in the Australian night time economy: A comparison of alcohol only versus alcohol and illicit drug consumption. (23rd October 2019) - Norman, Thomas; Peacock, Amy; Bruno, Raimondo; Chan, Gary; Morgan, Anthony; Voce, Isabella; Droste, Nicolas; Taylor, Nicholas; Coomber, Kerri; Miller, Peter G.
Abstract: Introduction and Aims: Associations between substance use and aggression may be amplified by simultaneous alcohol and illicit drug use. This study aims to compare differences in involvement in past aggression between people who use different substances while accounting for broader risk propensity. Design and Methods: Self‐reported data on past three‐month involvement in verbal and physical aggression (victim or perpetrator) were drawn from interviews conducted in night‐time entertainment districts in seven Australian cities ( n = 5078). Using inverse probability of treatment weighting techniques, participants who reported alcohol versus alcohol and illicit drug use on the night of interview (including ecstasy, cannabis and other illicit stimulant subgroups) were weighted on the basis of drug use risk covariates (e.g. alcohol consumed, gender) to determine differences in involvement in aggression involvement. Results: After weighting for covariates, individuals who reported consuming any illicit drug + alcohol and ecstasy + alcohol combinations were more likely to be involved in physical (33% and 105%, respectively) and verbal (36% and 116%, respectively) aggression in the previous 3‐months when compared to those who consumed alcohol only. Cannabis + alcohol and other illicit stimulant + alcohol combinations were no more likely to be involved in either forms of aggression. Discussion and Conclusions: The likelihood of having been involved in past aggressive incidents was higher among those who reported any illicit drug + alcohol and ecstasy + alcohol combinations than those who reported alcohol exclusively, after accounting for covariates. These findings highlight individuals that may benefit most from the development of tailored health promotion/preventative safety interventions in night‐time settings.